IMPLEMENTASI PERAN BALAI PEMASYARAKATAN TERHADAP PEMENUHAN HAK KESEHATAN MENTAL ANAK BINAAN: Indonesia - Rasika Alivia; Diah Gustiniati Maulani; Emilia Susanti; Ahmad Irzal Fardiansyah; Dita Trijayanti (Muhammadiyah Law Review Journal, 2026)
One of the problems arising from the increasing involvement of children in criminal activity is the fulfillment of mental health rights during the criminal justice process. The success of rehabilitation and social reintegration can be affected by the psychological stress that children in conflict with the law may experience as a result of social stigma, separation from family, and developmental processes. Therefore, Correctional Institutions (BAPAS) play a crucial role in guaranteeing the mental health rights of inmates. This study used a descriptive-analytical approach, an empirical-legal approach, and a normative-empirical approach. Data were collected through interviews with Community Guidance Officers, inmates, and academics, as well as through a literature review. Furthermore, a qualitative analysis was conducted. The findings indicate that BAPAS has successfully fulfilled its role in fulfilling mental health rights through the implementation of normative, ideal, and factual aspects. These aspects include mentoring, community research, counseling, religious guidance, recreational activities, facilitation of psychological services, and social reintegration programs. Legal factors, law enforcement, and facilities and infrastructure serve as supporting factors, while societal and cultural factors remain major obstacles due to social stigma, low acceptance of children in conflict with the law, and limited understanding of mental health. Therefore, it is necessary to strengthen cross-sector coordination, increase the capacity of Community Guidance Officers, and develop mental health service standards to optimize the protection of the rights of foster children.